2013
DOI: 10.1080/00949655.2013.829059
|View full text |Cite
|
Sign up to set email alerts
|

Considering Taguchi loss function on statistically constrained economic sum of squares exponentially weighted moving average charts

Abstract: In this paper, Duncan's cost model combined Taguchi's quadratic loss function is applied to develop the economic-statistical design of the sum of squares exponentially weighted moving average (SS-EWMA) chart. The genetic algorithm is applied to search for the optimal decision variables of SS-EWMA chart such that the expected cost is minimized. Sensitivity analysis reveals that the optimal sample size and sampling interval decrease; optimal smoothing constant and control limit increase as the mean and/or varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Lu et al [37] proposed the economic-statistical design of the MaxEWMA chart and showed that the design increases the quality cost slightly, but effectively improves the detection ability in small process mean and/or variability shifts. For more extensive studies on the economic-statistical design of a single chart, we refer to Huang and Lu [38], Lu and Huang [39], and Lu [40].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [37] proposed the economic-statistical design of the MaxEWMA chart and showed that the design increases the quality cost slightly, but effectively improves the detection ability in small process mean and/or variability shifts. For more extensive studies on the economic-statistical design of a single chart, we refer to Huang and Lu [38], Lu and Huang [39], and Lu [40].…”
Section: Introductionmentioning
confidence: 99%